2011
DOI: 10.1177/2045125311423781
|View full text |Cite
|
Sign up to set email alerts
|

SSRI-induced coagulopathy: is it reality?

Abstract: In patients with depression, fluoxetine increases bleeding time whereas escitalopram has no effect on coagulation profile. However, both the drugs can be used safely for long-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…One concern could be increased risk of bleeding with OAT in this population, 43 possibly related to increased alcohol use, 44 , 45 , 46 poorer anticoagulation control for patients receiving a vitamin K antagonist, 43 and greater likelihood of receiving antidepressants with anticoagulant effects. 47 , 48 , 49 Alcohol abuse was more common among patients with bipolar disorder or schizophrenia vs the matched reference groups, and although the fully adjusted models accounted for this factor, we cannot discern the potential relevance of alcohol use below the diagnosis threshold.…”
Section: Discussionmentioning
confidence: 99%
“…One concern could be increased risk of bleeding with OAT in this population, 43 possibly related to increased alcohol use, 44 , 45 , 46 poorer anticoagulation control for patients receiving a vitamin K antagonist, 43 and greater likelihood of receiving antidepressants with anticoagulant effects. 47 , 48 , 49 Alcohol abuse was more common among patients with bipolar disorder or schizophrenia vs the matched reference groups, and although the fully adjusted models accounted for this factor, we cannot discern the potential relevance of alcohol use below the diagnosis threshold.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). As SSRI antidepressants may collaterally perturb extrinsic pathway factors 46 47 , changes in extrinsic pathway proteins may be associated with the increased risk of suicidal behavior observed in depressed patients during the first month of SSRI therapy 48 . As an interesting tangent for future investigation, our previously published metabolomic findings have also shown that suicide attempters occupy a phenotypic “middle ground” with respect to plasma levels of alanine, glycine, and glucose 16 .…”
Section: Discussionmentioning
confidence: 99%
“…ve fluoksetinin hemotolojik parametreler üzerine etkisinin karşılaştırıldığı bir izlem çalışmasında 3. ayın sonunda fluoksetin kullanan hastalarda kanama zamanının başlangıç dönemine göre uzadığı ancak normal sınırlarda kaldığı belirlenmiş, bu durum; koagülopatilerin SSGİ kullanımı için kontrendikasyon teşkil etmediği ve hemotolojik hastalığı olan ile major cerrahi uygulanacak hastalarda güvenle kullanılabileceği şeklinde yorumlanmıştır 13 . Literatürde paroksetin ile ilişkilendirilen kanama bozukluğu gelişen olguların çoğunda paroksetinin kesilmiş ve nefazodon, essitalopram ve bupropion gibi ilaçlarla tedaviye devam edilmiştir 14 .…”
Section: Essitalopramunclassified